Mosque construction : differences between the traditional and modern Malaysian mosques / Ilyana Sujak, Anuar Talib and Mohd Mujib Mustaffa - Sujak, Ilyana; Talib, Anuar; Mustaffa, Mohd Mujib (2012)
The Islamization of the Malay world since the Melakan Sultanate has transformed almost the entire structures of the Malay society in various aspect of life, from the religious to the social, as well as economic and political. The worldviews of the traditional Malays were transformed into the Islamic doctrine and it became the foundation that shaped their lives including the architectural facet. The mosque architecture has always been regarded as a landmark for the local traditional Islamic community and its cultural expression. However, since the middle of the 19th Century, influence by European colonists and the modern thoughts of the early 20th Century have changed the political, economic and technological fabric of Islamic communities of the Malay Peninsula. It had caused a change in the official institution and the construction of mosques. The modern Muslim world was faced with a new political structure, construction industry and building technology that resulted to the marginalizing of the position and role of mosque in the Malay society. Even though the liturgical function of the mosque remain unchanged since 1400 years, its role and the intention behind its building construction, extensions and maintenance have changed. Therefore, some basic principles of traditional Malay mosque construction differ to that of the Modern mosques. Thus the main endeavor for this paper is to explore the differences between the traditional Malay mosques and modern mosques architecture particularly in the intention (niyya), the design and planning of the mosque, the structural and construction method, choice of building material, alongside community participation on the erection and maintenance of a mosque. Referring to traditional and modern mosques of the Malay Peninsula, some examples will be highlighted to ascertain the differences. It is critical to identify and understand the differences in the aspect of design and construction of traditional and modern mosques in order to design better mosques for the Muslim communities in the future.